Mozart Effect on Seizure Activity in The EEG - J Gordon Millichap (Pediatric Neurology Briefs, 1998)
The “Mozart Effect” on epileptiform activity in the EEG of 29 patients, ages 3-47 years, was investigated using brain maps and computerized analyses at the University of Illinois Medical Center, Chicago, IL.